Service Quality and Digitalized System for Motor Vehicle Testing in Makassar (Case Study of the Makassar City Transportation Agency's Motor Vehicle Testing Technical Implementation Unit (UPTD) in 2024) - Risdianto Risdianto; Mujahid Mujahid; Nurmadhani Fitri Suyuthi (Journal of Management and Administration Provision, 2025)
This study aims to analyze the influence of service quality and the implementation of a digitalization system on the effectiveness of motor vehicle inspection services in Makassar City. The background of this research is based on the local government's efforts to improve transparency, efficiency, and accountability in the vehicle inspection process, in line with developments in information technology. The research method used is a qualitative approach with a descriptive method applied to users of vehicle inspection services, as well as interviews with technical officers.  The results show that service quality comprising reliability, responsiveness, assurance, empathy, and tangible aspects has a significant impact on user satisfaction. In addition, the implementation of digital systems, such as online registration and integration of vehicle test data, has had a positive effect on time efficiency, ease of access, and the reduction of potential illegal levies. The conclusion of this study affirms that improving service quality and digitalization systems simultaneously supports the development of better, more transparent, and accountable public services in the motor vehicle inspection sector.